Strategi Coping pada Mantan Penganut Aliran Sesat - Khairunnisa Putri; Sri Kushartati (Universitas Islam Indonesia, 2015)
This study aims to find out about the coping strategies on the former follower of a cult andthe factors that influence them. Two respondents participated in this study. The method in thisstudy uses a qualitative method with a phenomenological approach. The results of this studyindicate that the two respondents perform coping strategy to reduce pressure felt. They useemotional focused coping in the form of distancing, escape avoidance, self-control, acceptingresponsibility, positive reappraisal, and denial. Planfull problem solving is used as a form ofproblem-focused coping. Known to both the subject of coping processes that vary in shape using coping strategies influenced by physical health factors, problem solving skills, and social skills.